Intensive care unit-acquired pneumonia due to Pseudomonas aeruginosa with and without multidrug resistance. Issue 2 (February 2017) - Fernández-Barat, Laia; Ferrer, Miquel; De Rosa, Francesca; Gabarrús, Albert; Esperatti, Mariano; Terraneo, Silvia; Rinaudo, Mariano; Li Bassi, Gianluigi; Torres, Antoni
Summary: Objective: Pseudomonas aeruginosa often presents multi-drug resistance (MDR) in intensive care unit (ICU)-acquired pneumonia (ICUAP), possibly resulting in inappropriate empiric treatment and worse outcomes. We aimed to identify patients with ICUAP at risk for these pathogens in order to improve treatment selection and outcomes. Methods: We prospectively assessed 222 consecutive immunocompetent ICUAP patients confirmed microbiologically. We determined the characteristics, risk factors, systemic inflammatory response and outcomes of P. aeruginosa pneumonia (Pa-ICUAP), compared to other aetiologies. We also compared patients with MDR vs . non-MDR Pa-ICUAP. Results: Pseudomonas aeruginosa was the most frequent aetiology (64, 29%); 22 (34%) cases had MDR. Independent predictors for Pa-ICUAP were prior airway colonization by P. aeruginosa, previous antibiotic treatment, solid cancer and shock; alcohol abuse and pleural effusion were independently associated to lower risk for Pa-ICUAP. Chronic liver disease independently predicted MDR among Pa-ICUAP. The inflammatory biomarkers were similar between all groups. Patients with Pa-ICUAP had lower unadjusted 90-day survival (p = 0.049). However, the 90-day survival adjusted for confounding factors using a propensity score did not differ between all groups. Conclusion: Pseudomonas aeruginosa remains the most frequent aetiology of ICUAP, with high prevalence of MDR. These risk factors should be taken into account to avoid inappropriate empiric antibiotics for Pa-ICUAP. Pseudomonas aeruginosa, regardless multidrug resistance, was not associated with different propensity-adjusted survival. Highlights: P. aeruginosa remains the most frequent pathogen causing ICUAP. Prior airway colonization by P. aeruginosa, previous antibiotics are independent predictors of P. aeruginosa ICUAP. Chronic liver disease independently predict multi-drug resistance of P. aeruginosa ICUAP. P. aeruginosa ICUAP is not associated to propensity-adjusted worse survival.